Species-dependent structural polymorphism of Y145Stop prion protein amyloid revealed by solid-state NMR spectroscopy - Theint Theint (Nature Portfolio, 2017)
Prion diseases can be transmitted across species. Here the authors use solid-state NMR to study prion protein (PrP) amyloids from human, mouse and Syrian hamster and show that their structural differences are mainly governed by two residues, which helps to understand interspecies PrP propagation on a molecular level.